2018
DOI: 10.26480/mjhr.02.2018.15.18
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Lentil Germplasm Against Stemphylium Blight by Observing Disease Reaction in Three Different Stages

Abstract: Stemphylium blight of lentil (Stemphylium botryosum) a standout amongst the most vital constraints of lentil production in Bangladesh. An investigation was carried out at the Regional Agricultural Research Station (RARS), Bangladesh Agriculture Research Institute (BARI), Rahmatpur, Barisal to pick out lentil germplasms against Stemphylium blight. Under the present study 100 lentil lines and 2 check varieties were evaluated for their reaction to Stemphylium blight and yield performance under natural epiphytotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Additionally, difficulty in sporulation and conidia production under laboratory conditions, especially of S. botryosum, imposes a great affliction for intervening blight risk. Moreover, previous findings were limited to the screening of lentil genotypes against S. botryosum (Podder et al, 2013;Das et al, 2017;Razzak et al, 2018) and A. alternata (Roy et al, 2021). To the best of our knowledge, this is the first report of successful isolation of S. botryosum in India and further confirmation of the pathogen through sequencing by using ITS and Stemphylium-specific gpd1 and gpd2 primers.…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, difficulty in sporulation and conidia production under laboratory conditions, especially of S. botryosum, imposes a great affliction for intervening blight risk. Moreover, previous findings were limited to the screening of lentil genotypes against S. botryosum (Podder et al, 2013;Das et al, 2017;Razzak et al, 2018) and A. alternata (Roy et al, 2021). To the best of our knowledge, this is the first report of successful isolation of S. botryosum in India and further confirmation of the pathogen through sequencing by using ITS and Stemphylium-specific gpd1 and gpd2 primers.…”
Section: Discussionmentioning
confidence: 87%
“…It is rising as a serious threat in West and South Asia, North America, and severely spread as a minor disease in Saskatchewan, Canada (Yadav et al, 2017). Previous works conducted in Bangladesh and India measured 62% of losses and sometimes complete crop failure was resulted due to extensive defoliation during the early stage of the pod setting (Razzak et al, 2018;Alam et al, 2017a). Since then, it has got prominence due to its increased occurrence and severity in many other countries like Hungary, Canada, Australia, Egypt, Syria, USA, Iran (Chen et al, 2009).…”
Section: Geographical Distributionmentioning
confidence: 99%
“…The prevalence of Stemphylium blight in most of the varieties was found maximum during the flowering stage followed by pod setting stage and maturity stage but it may differ with varieties. It results in huge economic loss due to the production of low quantity and quality of grain and seed (Razzak et al, 2018).…”
Section: Economic Importancementioning
confidence: 99%
“…So to feed the huge population and for sustainable food security, identification of blight resistant genotypes is must. Previous studies identified various lentil lines as Resistant, Moderately Resistant, Moderately Susceptible and Susceptible at different growth stages (Razzak et al, 2018). The present research was carried out to compare yield and yield characters of 40 moderate resistant lines of lentil and screening best genotypes for future use.…”
Section: Introductionmentioning
confidence: 98%